2016
DOI: 10.1371/journal.pone.0159796
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Excretory and Secretory Proteins of Haemonchus contortus (HcESP) Binding to Goat PBMCs In Vivo Revealed Stage-Specific Binding Profiles

Abstract: Haemonchus contortus is a parasitic gastrointestinal nematode, and its excretory and secretory products (HcESPs) interact extensively with the host cells. In this study, we report the interaction of proteins from HcESPs at different developmental stages to goat peripheral blood mononuclear cells (PBMCs) in vivo using liquid chromatography-tandem mass spectrometry. A total of 407 HcESPs that interacted with goat PBMCs at different time points were identified from a H. contortus protein database using SEQUEST se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 119 publications
(134 reference statements)
5
77
0
Order By: Relevance
“…In our previous research, tropomyosin was identified as an excretory and secretory protein (ESP) that binds to goat PBMCs at the L4 and L5 developmental stages of H. contortus [20], and we also demonstrated that HcESPs exhibit suppressive regulatory roles in their interaction with PBMCs [21]. In our recent study, recombinant tropomyosin was found to have high immunodiagnostic potential for early stage diagnosis of H. contortus infection in goats [22].…”
Section: Introductionmentioning
confidence: 87%
“…In our previous research, tropomyosin was identified as an excretory and secretory protein (ESP) that binds to goat PBMCs at the L4 and L5 developmental stages of H. contortus [20], and we also demonstrated that HcESPs exhibit suppressive regulatory roles in their interaction with PBMCs [21]. In our recent study, recombinant tropomyosin was found to have high immunodiagnostic potential for early stage diagnosis of H. contortus infection in goats [22].…”
Section: Introductionmentioning
confidence: 87%
“…Antigenicity, sensitivity and specificity may be influenced by the secretion time of antigen. It has been reported earlier that rHc-CS releases at 14 and 60 D.P.I and antibodies against this molecule are produced [23]. Another possibe reason might be the type of antigen used in study.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, recombinant protein, having high immunoreactive concentration, may act as best immunodiagnostic antigen by achieving high sensitivity and specificity [29][30][31][32][33][34][35][36]. Recombinant Hc-CS is a major constituent of HcES proteins [23] which may have potential to diagnose H. contortus at early stage of infection. This study was designed to evaluate the specific antibodies detection during early and late infections of H. contortus using immunoblotting and indirect-ELISA based on rHc-CS in experimentally infected goat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in the proteomic analysis of ESPs from H contortus , EF‐1α protein was recognized as binding molecule to goat PBMCs at L4, L5 and early adult developmental stages of H contortus in vivo 23 . Meanwhile, the immuno‐suppressant role of HcESPs on goat PBMCs in vitro was also demonstrated 24 .…”
Section: Introductionmentioning
confidence: 99%